ANALYSIS OF THE ROLE OF EMOTIONAL INTELLIGENCE INCREASING LEARNING MOTIVATION CRITICAL PEDAGOGIC PERSPECTIVE - Fian, Khafifatul; Roqib, Moh. (Jurnal Kajian Pendidikan dan Psikologi, 2025)
This paper aims to analyse the role of emotional intelligence in enhancing students' learning motivation from Daniel Goleman's perspective. The method used by the author is a literature review, collecting data from primary sources, particularly the book "Emotional Intelligence: Why It Can Matter More Than IQ" by Daniel Goleman. This is supplemented with findings from previous research relevant to the studied topic. After data collection, a selection process is conducted, followed by a conclusion. The data is then analysed descriptively and further examined through content analysis. The study results reveal that, as explained by Goleman, emotional intelligence refers to the ability to monitor and manage oneself and others regarding emotions, feelings, and behaviours. Students with good emotional intelligence tend to have higher learning motivation. Emotional intelligence plays a role in learning motivation by enhancing stress management, fostering perseverance, building self-awareness, encouraging a positive attitude toward learning, and improving the ability to cope with failure.